UR:BAN Human Factors in Traffic Approaches for Safe, Efficient and Stress-free Urban Traffic (ATZ/MTZ-Fachbuch, 2018)
The UR:BAN MV project funded by the German Federal Ministry for Economic Affairs and Energy BMWi focused specifically on the user of future vehicle assistance and information systems. In the case of advanced driver assistance systems for urban areas, the primary emphasis is safety in combination with efficiency and comfort. Research institutes and automotive industry have investigated human-vehicle interaction and behaviour of different traffic participants. This book gives a unique and comprehensive insight into the results. Driver assistance and information systems were optimized for use in urban settings. Furthermore, innovative test regimes for controllability testing and new evaluation techniques like networked simulators and virtual reality test-beds are described including statistical methodologies. The Content UR:BAN - the program.- Human Factors in Traffic.- Urban Driving.- Human-Machine Interaction for Urban Environments.- Behaviour Prediction and Intention Detection.- Simulation and Modelling.- Controllability and Safety. The Target Groups Automotive Engineers and Human Factors Experts - Researchers in the area of traffic psychology and human factors in traffic - Students in human factors, information technology, mechanical and electrical engineering The Editors Prof. Klaus Bengler, Head of Chair of Ergonomics, Technical University of Munich; Project Leader UR:BAN MV "Human Factors in Traffic" Dr. Julia Drüke (born Werneke), Senior Expert Driver Interaction, Volkswagen AG, Group Research; Subproject Leader UR:BAN MMI "Human-Machine Interaction for Urban Environments" Dr. Silja Hoffmann, Head of Research Group on Modelling and Simulation, Technical University of Munich; Assistant Subproject Leader UR:BAN SIM "Simulation" Dr. Dietric h Manstetten, Chief Expert Human-Machine Interaction, Robert Bosch GmbH; Subproject Leader UR:BAN VIE "Behaviour Prediction and Intention Detection" Alexandra Neukum, Head of Research Group on Traffic Sciences, Würzburg Institute for Traffic Sciences GmbH; Subproject Leader UR:BAN KON "Controllability".